2017
DOI: 10.1021/acs.chemrestox.7b00278
|View full text |Cite
|
Sign up to set email alerts
|

The Capture of Cadmium by Reactive Polysulfides Attenuates Cadmium-Induced Adaptive Responses and Hepatotoxicity

Abstract: Cadmium (Cd) is an environmental electrophile that modifies protein nucleophiles, thereby modulating cellular signaling and toxicity. While reactive persulfides/polysulfides exhibit relatively high nucleophilic properties, their roles in the altered gene expression and toxicity caused by Cd remain unclear. Exposing primary mouse hepatocytes to Cd caused heat shock protein 70 (HSP70) and metallothionein (MT)-I/II to be upregulated and cytotoxicity to occur. These effects were blocked in the presence of polysulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 56 publications
(92 reference statements)
2
23
0
Order By: Relevance
“…This indicates that RSS are involved in the repression of electrophile-mediated toxicity by the formation of inactive metabolites of electrophiles. Consistent with this notion, the toxicity of MeHg, Cd and 1,4-NQ was effectively blocked by treatment with the model polysulfide Na 2 S 4 [75,77,80].…”
Section: Protective Function Of Rss Against Electrophilic Stresssupporting
confidence: 54%
See 3 more Smart Citations
“…This indicates that RSS are involved in the repression of electrophile-mediated toxicity by the formation of inactive metabolites of electrophiles. Consistent with this notion, the toxicity of MeHg, Cd and 1,4-NQ was effectively blocked by treatment with the model polysulfide Na 2 S 4 [75,77,80].…”
Section: Protective Function Of Rss Against Electrophilic Stresssupporting
confidence: 54%
“…As noted above, electrophiles can be captured by RSS, leading to the formation of their sulfur adducts. For example, we previously reported that MeHg, Cd, 1,4-NQ and NAPQI, which is the toxic metabolite of acetaminophen, can react with RSS, such as H 2 S, CysSSH, GSSH, GSSSG or the model polysulfide Na 2 S 4 , leading to the formation of bismethylmercury sulfide [(MeHg) 2 S], cadmium sulfide (CdS), CdS 2 O 3 , 1,4-NQ-SH, 1,4-NQ-S-1,4-NQ, 1,4-NQ-S-1,4-NQ-OH, NAPQIH 2 -SSSCys, NAPQIH 2 -SSCys and NAPQIH 2 -SSG [5,12,[75][76][77][78]. Additionally, (MeHg) 2 S and NAPQIH 2 -SSSCys were identified as novel metabolites of MeHg and acetaminophen from the liver and urine of mice treated with these compounds [78,79].…”
Section: Protective Function Of Rss Against Electrophilic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In bovine aortic endothelial cells, CSE knockdown potentiated Cd-induced cytotoxicity but CSE overexpression provided protection [43]. In vivo experiments showed that CSE-knockout mice were sensitive to Cd-induced hepatotoxicity [44]. Adaptive changes in the activity and expression of CGL, MST, and TST in various frog tissues in response to exposure to lead, mercury, and cadmium confirmed the protective function of these enzymatic proteins against electrophilic stress [45,46].…”
Section: Physiological Functions Of H 2 S and Polysulfidesmentioning
confidence: 79%